Aminoglycoside extended interval dosing in neonates is safe and effective: a meta-analysis. Issue 4 (27th April 2005) - Nestaas, E; Bangstad, H-J; Sandvik, L; Wathne, K-O
Abstract : Objectives: To review the evidence from controlled clinical trials of neonates given equal daily aminoglycoside doses as extended interval dosing (dosage interval typically 24 hours in term and 36–48 hours in immature neonates) compared with traditional dosing (dosage interval typically 8–12 hours in term and 12–24 hours in immature neonates). Design: Systematic review and meta-analysis of controlled trials found in electronic databases, trial registers, and references in reviews and selected trials. Settings: The selected trials were blinded and assessed for methodological quality. Each trial's own predefined criteria for treatment failure, nephrotoxicity, ototoxicity, and therapeutic serum drug concentrations were used. Subjects: Controlled trials of neonatal aminoglycoside treatment in which equal aminoglycoside daily doses were given at traditional and extended dosage intervals. Main outcome measures: Serum drug concentrations outside the therapeutic range. Treatment failure and toxicity. Results: Sixteen trials involving 823 neonates met the inclusion criteria for the systematic review. Twelve trials involving 698 neonates were included in the meta-analysis of the pharmacokinetics. Compared with traditional dosing, extended interval dosing was associated with a significantly lower risk of both peak (summary risk ratio 0.50, 95% confidence interval 0.26 to 0.94) and trough (0.36, 0.25 to 0.56) serum drug concentrations outside the therapeutic range. Accurate information on treatment failure was obtained in nine trials involving 555 neonates. One trial reported treatment failure. In this trial two neonates in the traditional dosing group did not respond to treatment within 72 hours. Nephrotoxicity was investigated in 589 neonates in 12 trials and ototoxicity in 210 neonates in four trials, with no significant differences between the two dosing regimens. Conclusions: Extended interval dosing of aminoglycosides in neonates is safe and effective, with a reduced risk of serum drug concentrations outside the therapeutic range.